Perioperative safety: learning, not taking, from aviation - Neuhaus, Christopher; Hofer, Stefan; Hofmann, Götz-Ulrich; Weigand, Markus A.; Lichtenstern, Christoph (Anesthesia & analgesia, 2016)
An abstract is unavailable.
Accepted for publication February 25, 2016
Gesehen am 16.08.2019